Revealing the Mechanism of Huazhi Rougan Granule in the Treatment of Nonalcoholic Fatty Liver Through Intestinal Flora Based on 16S rRNA, Metagenomic Sequencing and Network Pharmacology - Liu, Yingying; Tan, Yingying; Huang, Jiaqi; Wu, Chao; Fan, Xiaotian; Stalin, Antony; Lu, Shan; Wang, Haojia; Zhang, Jingyuan; Zhang, Fanqin; Wu, Zhishan; Li, Bing; et al. (Frontiers in Pharmacology, 2022)
Background: The incidence of Nonalcoholic Fatty Liver (NAFL) is increasing year by year, growing evidence suggests that the intestinal flora plays a causative role in NAFL. Huazhi Rougan Granule (HRG) is commonly used in the clinical treatment of NAFL. It is reported that it can reduce lipids and protect the liver, but no research has confirmed whether the drug's effect is related to intestinal flora. Therefore, we investigated whether the effect of HRG is related to the regulation of intestinal flora to further explore the mechanism of HRG in the treatment of NAFL through intestinal flora. Methods: In this study, C57BL/6J mice were fed a high-fat diet for 8 weeks, and the high-fat diet plus HRG or polyene phosphatidylcholine capsules were each administered by gavage for 4 weeks. High-throughput sequencing, network pharmacology, and molecular docking were used to explore the mechanism of HRG in the treatment of NAFL through intestinal flora. Results: HRG treatment can reduce body weight gain, lipid accumulation in liver and lipogenesis and reduce serum biochemical indexes in high-fat-fed mice. Analysis of intestinal flora showed that HRG changed the composition of intestinal flora, which was characterized by a decrease in the Firmicutes/Bacteroidetes ratio. Moreover, the species distribution was significantly correlated with AKP, HDL-C, and TG. Metagenetic analysis showed that HRG altered the functional composition and functional diversity of microorganisms, which was mainly characterized by an increase in the abundance of metabolic pathways. The network pharmacology results show that the mechanism of HRG in the treatment of NAFL through intestinal flora is mainly reflected in the biological process of gene function and related to infectious diseases, immune systems, and signal transduction pathways, such as cytokine-cytokine receptor interaction, Chagas disease, IL-17 signaling pathway and other signaling pathways. Conclusion: These results strongly suggest that HRG may alleviate NAFL by preventing IFD.